Molecular Detection and Diagnosis of Phytoplasma Infection in Cassava (Manihot esculenta Crantz) in Eastern Visayas, Philippines - Erlinda A, Vasquez,; Lucia M, Borines,; Fatima G, Palermo, Lady (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Phytoplasma disease is a threat to the cassava industry but little is known about the disease in the country. This study was conducted to develop and optimize a protocol for the detection of phytoplasma and determine the existence of phytoplasma strains in the different cassava growing areas in Eastern Visayas, Philippines. PCR reaction using primer pair PA2F/R and nested primer pair NPA2F/R as well as the use of primer pair P1/P7 followed by nested primer pair R16F2n/R2 with slight modifications in the thermocycling conditions detected phytoplasma infecting cassava. Ten out of the eleven areas in Eastern Visayas, a scale insect and a cassava grown from tissue culture tested positive for phytoplasma using nested primer pairs NPA2F/R and R16F2n/R16R2. Six band patterns were detected when NPA2F/R primer amplicons were digested with RsaI and MspI restriction enzymes suggesting that more than one strain of phytoplasma infect cassava.